(3QSGdI aj bhGYO GdefWb hCMcGegs ((3eMeO Hf CHj GdWjH s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPg Led JfVHW HgG bhGYO GdefWb hCMcGeg OdGdI GddaX Ydi GdeYfi dhVYg dg eWGHbI s
(3BNQgG (B:s
(3dGecGf GdMdh hEf cGfJ eGfYJg GdNdh aYdi GdYcSjf hgPG eG bUOfG PcQg ai gPG GdeNJUQ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(640) s
Keywords: (3GdadSaI hGdefWbs